2009
DOI: 10.1002/pen.21488
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cellular structure heterogeneity and anisotropy of polypropylene and polypropylene nanocomposite foams

Abstract: This article presents the analysis of the processing parameters\ud influence on the foaming behavior and cellular\ud structure of PP-montmorillonite foams. Polypropylene\ud nanocomposites containing 5.0 phr of an organically-\ud modified montmorillonite (MMT) were initially\ud melt-compounded in a twin-screw extruder with azodicarbonamide\ud (ADC) and later foamed using a one-step\ud compression-molding process. The cellular structure\ud and morphology of the foams was assessed using both\ud scanning and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…On the one hand, by filling PP with inorganic compounds such as talc or nanoparticles [10][11][12] and on the other hand by using special PP grades known as high melt strength PPs, on which by promoting a high degree of branching the melt strength is significantly increased [6,11,13]. Finally the less desirable solution because turn the polymer non-recyclable, is crosslinking the PP matrix [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, by filling PP with inorganic compounds such as talc or nanoparticles [10][11][12] and on the other hand by using special PP grades known as high melt strength PPs, on which by promoting a high degree of branching the melt strength is significantly increased [6,11,13]. Finally the less desirable solution because turn the polymer non-recyclable, is crosslinking the PP matrix [1].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the addition of silicate-layered nanoclays, particularly montmorillonite, promotes the formation of polymer foams with more homogeneous cellular structures, resulting in improved mechanical performances due to a combination of the addition of the stiffer particles and a finer foam cellular structure. 11,12 Carbon-based nanofillers, such as carbon nanotubes, carbon nanofibres or graphene, have increasingly been incorporated into polymers in the last years looking not only for mechanical enhancement but mainly for improving their commonly low conduction properties. From these, graphene has attracted a great deal of interest due to its unique combination of properties, 13 which include a very high thermal conductivity and high tensile strength, 14 as well as a particular flat morphology, 15 enabling its use as mechanical reinforcement of polymers at very low concentrations 16,17 and making it suitable for the development of new conductive polymer composites for sectors such as electronics.…”
Section: Introductionmentioning
confidence: 99%
“…The MMT nanoparticles thermally stabilize the PP foams during expansion, and this effect is even more pronounced with an increase in ADC content [54]. [44] In EPDM/clay foamed nanocomposites modified by maleic anhydride, an increase in mechanical and dynamic mechanical properties, as well as in non-isothermal crystallization rate, has been observed [55].…”
Section: Expanded Polyolefin-based Foamsmentioning
confidence: 95%